2003
DOI: 10.2355/isijinternational.43.1326
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reverse Emulsification and Mixing Time in a Bottom Blown Bath Covered with Top Slag

Abstract: Water model experiments were carried out to seek a possibility to control reverse emulsification, i.e., entrapment of slag droplets and mixing time in the molten metal layer covered with top slag. The bath was agitated by centric bottom gas injection. A circular plate was immersed in the bath to change the flow pattern. When the diameter of the plate was larger than the width of the bubble dispersion region formed above the centric nozzle, the recirculating flow was significantly strengthened. As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…(a) 1cSt = 1centistokes = 0.01cm²/s = 0.000001m²/s; (b) Yamashita and Iguchi (2003); (c) measured values.…”
Section: Thymol Mass Transfer In An Oil-aqueous Solution Systemmentioning
confidence: 99%
“…(a) 1cSt = 1centistokes = 0.01cm²/s = 0.000001m²/s; (b) Yamashita and Iguchi (2003); (c) measured values.…”
Section: Thymol Mass Transfer In An Oil-aqueous Solution Systemmentioning
confidence: 99%
“…1 Therefore, developing a technology for introducing alloy addition to steel also during the course of continuous casting is one approach for enhancing the steelmaking process, especially as the effective introduction of micro-additives or non-metallic inclusion modifiers to the liquid steel is the key to the production of the highest quality steel. [2][3][4] During secondary metallurgy treatment, introduced alloy additions mix with the steel due to metal circulation induced by stirring the metal bath with inert gas. Therefore, during the injection of inert gases care must be taken to correctly select the intensity of gas flow so as to minimise the phenomenon of the slag phase being washed away over the gas permeable block and the slag phase emulsifying with the liquid steel.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed an empirical equation for calculation of mixing time. Yamashita and Iguchi 5,6 reported that mixing time increases due to the presence of an upper buoyant phase because recirculating flows are suppressed and reverse emulsification takes place. The entrapment of many oil droplets in the water layer weakened the large scale recirculating flow in the bath, and hence prolonged the mixing time.…”
Section: Introductionmentioning
confidence: 99%